Estudo clássico, quântico e semi-clássico em colisões elásticas para o sistema He2 - Marcio Oliveira Alves (2012)
Classical, semi-classical and quantum formalism were used to study helium-helium collisions, both in a direct and inverse approach. Potential quality were quantified by comparing simulated cross section and bound state with experimental data. Firsov approach was used to recover potential energy function from experimental differential cross section. The algorithm was also tested against simulated experimental errors in the differential cross section. Quantum phase shift accumulated along the scattering coordinates and angular momentum is essential to calculate bound state properties and cross section. This phase shift was calculated by the Born approximation, by the variable phase method and by the Renormalizes Numerov approach. The semiclassical JWKB approach was used as guide to the quantum calculation. Efficiency and limitation of these four methods to establish the quantum phase is discussed. The sensitivity formalism was applied to analyse the potential parameters influence on the calculated properties